Habituation of Surya Mentari Program to Achieve the Quality of Reading the Qur'an at Muhammadiyah Suronatan Elementary School - Djirzanatil Muchtaromah (Early Publishing, 2026)
Qur'anic education at the elementary school level plays a strategic role in fostering students' religious character while developing their competence in reading the Qur'an accurately according to the principles of tajweed and makharij al-huruf. However, the post-pandemic learning context has revealed that many students still experience difficulties in achieving the expected standards of Qur'anic reading proficiency. This study aims to analyze the implementation of the Surya Mentari Program (Suronatan Recites the Qur'an Every Day) and examine how its habituation-based approach contributes to improving students' Qur'anic reading quality. This research employed a qualitative field study using a descriptive case study design. The participants included the school principal, ISMUBA teachers, and fifth-grade students at SD Muhammadiyah Suronatan. Data were collected through observations, in-depth interviews, and documentation, and validated using source and technique triangulation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the Surya Mentari Program is systematically implemented through integrated stages of planning, implementation, and evaluation embedded within the school's culture. Continuous and structured habituation significantly improves students' fluency, accuracy in applying tajweed, and correctness of makharij al-huruf. The program also strengthens Qur'anic literacy, with students demonstrating reading achievement above the school's average Qur'anic literacy index. Beyond improving reading competence, the program contributes to the development of students' religious character, discipline, and learning motivation. These findings suggest that a habituation-based Qur'anic learning program is an effective strategy for enhancing Qur'anic reading quality and cultivating a sustainable culture of Qur'anic literacy in Islamic elementary schools.